The Effectiveness of Lactation Counseling on Knowledge, Self-Confidence, and Successful Breastfeeding for Postpartum Mothers - Elizabeth Widayati; Ranti Lestari; Novi Widiastuti (Universitas Islam Bandung, 2022)
The best primary nutrition for babies is breast milk. Exclusive Breastfeeding is given since the baby is born for six months. Breastfeeding proofed to reduce infant mortality and morbidity. The rate of exclusive breastfeeding in Indonesia is still low at around 37.3%. The cause of the low number of breastfeeding is the lack of information obtained by the mother, affecting the mother's knowledge and belief. Breastfeeding mothers need the correct information. This information can be obtained from lactation counseling provided by health workers. This study aims to analyze the effect of counseling on knowledge, mothers' self-confidence, and breastfeeding ability in postpartum mothers. This research was conducted in July–September 2021 in the working area of the Sukaluyu Public Health Center, Cianjur regency. This research method uses a quasi-experimental design with a post-test only with a control group design—the sample in this study was 60 respondents, primigravida mothers aged 37 weeks to 1 month postpartum. The analysis used is the t-test and the Mann-Whitney test. This study uses three instruments: knowledge, self-confidence in the form of a Breastfeeding Self-Efficacy Scale Form (BSESF) questionnaire, and a breastfeeding ability observation sheet. The study results on mothers' knowledge in the intervention group were higher, namely 26, and there was a significant difference between the knowledge of the two groups (p=0.03). There are differences in the beliefs of breastfeeding mothers after being given counseling (p=0.001). There is no difference in the mothers' ability of the two groups after counseling (p=1.000). In conclusion, lactation counseling using video media increases the knowledge and confidence of breastfeeding mothers compared to those given standard care.